TRANSLATION TECHNIQUE IN TRANSLATING INDONESIAN FABELS INTO ENGLISH - usep muttaqin; Nadia Gitya Yulianita; Uki Hares Yulianti (Lingua Scientia, 2021)
This paper aims to describe translation techniques used in translating Indonesian Fables into English. The data is taken from bilingual fable books from five different publishers. The research uses purposive sampling technique and also comparative method to analyze the data. The finding shows that there are nine translation techniques used by translators namely equivalence, literal translation, discursive creation, borrowing, variation, transposition, modulation, reduction, and deletion. Equivalence is the most frequently used technique followed by literal translation. For further study, researcher may pay attention on the accuracy of the translation and readability of the translated text.